Maple syrup urine disease of neonates report of two cases and review of literature - Chen, Zheng (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2010)
OBJECTIVE: To analyze and summarize clinical manifestation of maple syrup urine disease (MSUD) of neonates